2019
DOI: 10.1371/journal.pone.0220699
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is an effective predictor of difficult-to-wean and mortality among critically ill surgical patients

Abstract: Background Critically-ill surgical patients are at higher risk for sarcopenia, which is associated with worse survival. Sarcopenia may impair the respiratory musculature, which can subsequently influence the outcome of ventilator weaning. Although there are a variety of weaning parameters predictive of weaning outcomes, none have tried to incorporate “muscle strength” or “sarcopenia”. The aim of the current study was to explore the association between sarcopenia and difficult-to-wean (DtW) in crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 36 publications
3
55
0
2
Order By: Relevance
“…In this patient, the PLVI was mean psoas area (mm 2 )/vertebral body area (mm 2 ) ((695 + 708)/2)/1110 � 0.63. 4 Current Gerontology and Geriatrics Research [41][42][43], but there is some conflicting evidence regarding whether the psoas area is truly representative of the global skeletal muscle area [44]. Its routine use, particularly, in research studies, is, in part, secondary to convenience and simplicity of acquiring measurements, but it is suggested in the literature that the total lumbar muscle area may be more closely related to the overall muscle mass, and given that psoas comprises only 10% of the total trunk musculature, this may not be accurate [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, the PLVI was mean psoas area (mm 2 )/vertebral body area (mm 2 ) ((695 + 708)/2)/1110 � 0.63. 4 Current Gerontology and Geriatrics Research [41][42][43], but there is some conflicting evidence regarding whether the psoas area is truly representative of the global skeletal muscle area [44]. Its routine use, particularly, in research studies, is, in part, secondary to convenience and simplicity of acquiring measurements, but it is suggested in the literature that the total lumbar muscle area may be more closely related to the overall muscle mass, and given that psoas comprises only 10% of the total trunk musculature, this may not be accurate [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…(9) Using the same method of sarcopenia assessment, Kou et al found that sarcopenia was associated with prolonged weaning (more than seven days of weaning after the rst SBT) or need for reintubation within 48 hours after extubation in critically ill surgical patients in Taiwan. (8) There is no gold standard for sarcopenia assessment in the ICU. Although muscle mass can be measured by either bioelectrical impedance, dual X-ray absorptiometry, CT, magnetic resonance imaging, and ultrasonography, all these methods are preliminary research tools; their bedside and routine use is complex in ICU settings and limited to clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that decreased muscle mass and sarcopenia are associated with extubation failure and di culty in MV liberation. (8)(9)(10) These studies evaluated muscle mass using measurement of different skeletal muscle diameter on abdominal computed tomography (CT). However, CT-based analysis of body muscle mass has some prominent limitations such as radiation exposure, high cost, and the need to transport the patient outside of the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…All of the studies that were included were retrospective cohort studies, with the exception of one 34 , which was a prospective cohort study. A total of ve studies was conducted in the U.S. 10,23,24,33,34 ; while China 21,22 , Japan 17,35 , and the Netherlands 11,18 each had two studies, and Korea 20 , Australia 25 , and Brazil 19 each had one study respectively. All studies used CT to detect sarcopenia.…”
Section: Study Summarymentioning
confidence: 99%
“…There were several outcomes reported in our meta-analysis. Seven studies used in-hospital mortality 10,11,18,17,21,23,34 , four studies used 30-day mortality 19,22,25,35 , and three studies used 1-year mortality 20,24,33 . The proportion of males among the studies that were included ranged from 51.40% to 61.40% (Table 1).…”
Section: Study Summarymentioning
confidence: 99%